Study of asynchronous stereoscopic video based on event related potentials - SHEN Li-li; WU Zi-yang (工程科学学报, 2018)
When stereoscopic videos are transmitted on the no-quality-assurance internet, frame delay occurs in the left and right views, which affect the stereoscopic sensation as well as the viewing quality. In this paper, the stimulus of motion-in-depth and motionin-lateral asynchronous stereoscopic videos were analyzed and they were compared via qualitative and quantitative assessments. In this quantitative experiments, the well-known electroencephalogram (EEG) was utilized. A total of ten subjects was recruited to participate in an experiment, in which they watched randomly presented asynchronous stereoscopic video clips. For the qualitative assessment, after viewing one clip, the subjects were asked whether they perceived any asynchronicity in the frames. The degrees of asynchronicity included no delay, one frame delay, two frame delay, and three frame delay. The electroencephalogram (EEG) signal of each subject was recorded as they viewed the clip. Next, the event-related potentials (ERPs) were extracted from the EEG signals and the behavioral data and the ERPs were analyzed to compare the different reactions to the depths and lateral extents of the asynchronous stereoscopic motion. The results reveal that the maximum allowable asynchronicity perceived for motion-in-depth stereoscopic video clips is one frame, whereas there must be no delay in the motion-in-lateral stereoscopic video clips. In addition, compared with being stimulated by the motion-in-lateral asynchronous stereoscopic video clips, a magnitude of P300 has a wider range when the subjects are stimulated by motion-in-depth asynchronous stereoscopic video clips. This indicates that the brain becomes more active in this circumstance. At the same time, the latency of P300 is longer than when stimulated by the motion-in-lateral asynchronous stereoscopic video clips, which means that when the subjects are stimulated by the same degree of asynchronicity of motion-in-depth and -in-lateral stereoscopic video clips, more time is required to process the stimulation of motion-in-depth stereoscopic video clips.